IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN BAHASA INGGRIS, BAHASA ARAB, DAN SEJARAH KEBUDAYAAN ISLAM DI MA MARDHOTILLAH PONDOK PESANTREN HIDAYAHTULLAH - Dian Maulina,M.M; Marsya Bella; Yollanda; Suci Mardotila (STKIP Subang, 2026)
This study aims to determine the implementation of the Merdeka Curriculum in Islamic Cultural History, English, and Arabic learning at MA Mardhatillah Islamic Boarding School Hidayatullah. This research used a qualitative method through interviews, observations, and documentation. The results showed that the implementation of the Merdeka Curriculum has been carried out quite well through the use of various learning methods such as discussions, question and answer, role play, presentations, and games, so that students become more active and enthusiastic in learning. However, there are still several obstacles, such as differences in students’ abilities, limited vocabulary, low self-confidence, and limited learning facilities and media. Teachers attempt to overcome these obstacles by providing motivation, evaluation, additional guidance, and creating a conducive learning atmosphere. Overall, the implementation of the Merdeka Curriculum at MA Mardhatillah Islamic Boarding School Hidayatullah has been quite effective, although improvements in learning facilities are still needed so that curriculum objectives can be achieved optimally.